Bacteriological profile of blood stream infections among febrile patients attending a tertiary care centre of Western Nepal - Bhatta, Dharm Raj; Gaur, Abhishek; Supram, HS (Asian Journal of Medical Sciences, 2013)
Background Blood stream infections (BSI) are significant cause of morbidity and mortality in the world. This study was conducted to determine the common bacterial agents associated with BSI with their antimicrobial susceptibility patterns in a tertiary care centre in the Western region of Nepal. Method This cross-sectional study was conducted for a period of two years from May 2010 to May 2012. All patients with fever (temperature ≥ 38°C) were included in the study. Results A total of 4,145 patients with febrile illness were included in this study, bacterial agents were isolated in 251 (6%) cases. Common bacterial isolates were Salmonella spp., Klebsiella pneumoniae, Escherichia coli, Pseudomonas species, Acinetobacter species, Staphylococcus aureus and Coagulase negative Staphylococci. Paratyphoid fever (Caused by S. Paratyphi A) is more common than typhoid fever. The members of Enterobacteriaceae were found to be resistant to ampicillin and cefazolin. Majority of the nonfermenters were found to be sensitive to most antibiotics. Gentamicin and Ciprofloxacin were sensitive to majority of gram positive bacteria. Conclusion Gram-negative bacteria were the predominant causes of BSIs. The occurrence of drug resistance among the isolated bacteria is of great concern. Imipenem showed 100% sensitivity against Pseudomonas aeruginosa indicating lack or low level of MBL activity. DOI: http://dx.doi.org/10.3126/ajms.v4i3.8165 Asian Journal of Medical Sciences 4(2013) 92-98